[PP.01.31] THE EVOLUTION OF HYPERTENSIVE POPULATION IN THE INTERNAL MEDICINE WARD. (September 2017) - Rodrigues, J.; Ferreira Simões, A.; Freixa, M.; Úria, S.; Silva, G.
Abstract : Objective: Arterial hypertension (AH) is a major health concern because of its prevalence and deaths related to its complications, being important to acknowledge the way it is evolving. The authors intended to identify and characterize the differences between patients with the diagnosis of AH admitted to an Internal Medicine ward 4 years apart. Design and method: Observational retrospective study based on the collection of clinical data of patients admitted in an internal medicine ward during the year 2012 and 4 years later, in 2016. The hypertensive patients were divided in two groups: admitted in 2012 (H12); admitted in 2016 (H16). It was defined as cardiovascular event stroke or myocardial infarction (MI) as the motive of admission and registered all causes mortality. Results: Total sample includes 407 patients, from which 69.8% (n = 284) have the diagnosis of AH (n = 339). (1) From 2012 to 2016 there is a fall in the number of patients with AH (74, 5% in H12 vs 60, 7% in H16; p < 0, 001). (2) The female gender is more prevalent in both groups (51, 8%). (3) The mean age is superior in H16 (77, 9 ± 11, 4 vs 80, 4 ± 8, 7 years; p = 0, 042), as well as the length of stay (7, 9 ± 6, 6 vs 14, 4 ± 10, 6 dias; p < 0, 001). (4) There is a raise in the prevalence of other diseases in H16: heart failure (27, 1% vs 43, 5%; p = 0, 008); atrial fibrillation (26, 1% vs 38, 8%; p = 0, 035); obesity (8% vs 17, 6%; p = 0, 022); stroke (21, 1% vs 22, 4%; p = 0, 875). (5) The cardiovascular events (6% vs 8, 2%, p = 0, 604; stroke – 7% vs 8, 2%, p = 0, 805; MI – 2, 5% vs 3, 5%, p = 0, 7), death (6, 5% vs 9, 4%; p = 0, 002) or either one (14, 1% vs 21, 2%; p = 0, 160) become more frequent in H16. Conclusions: In the studied sample there is a decrease of the number of patients with AH, but at the same time there is a tendency of increase of the cardiovascular events and death in the hypertensive patients, highlighting the importance of prevention and control of these important cardiovascular risk factor.